2011
DOI: 10.1177/1742715011416890
|View full text |Cite
|
Sign up to set email alerts
|

Follower perceptions of the emotional intelligence of change leaders: A qualitative study

Abstract: We present and explore a follower-centric model of how employees perceive the emotional intelligence (EI) of change leaders. Qualitative investigations of EI are rare and have not explored the field of organizational change leadership. Accordingly, we analyse qualitative data from a series of interviews set within the context of organizational change. We examine follower attributions about the abilities of their leaders to manage and express their own emotions and to respond appropriately to the followers’ emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 111 publications
(302 reference statements)
0
24
0
Order By: Relevance
“…Additionally, Sauer and Kohls (2011) propose that mindfulness may benefit leadership by contributing to improvements in information processing, interpersonal interactions, and decision making. Others have suggested that mindfulness contributes to emotional intelligence which, in turn, contributes to higher positive affect, lower negative affect, and greater life satisfaction (Schutte and Malouff, 2011;Smollan and Parry, 2011). Indeed, recent research shows that increasing mindfulness contributed to more job satisfaction and less stress as a result of increased ability to regulate one's emotions (Hülsheger et al, 2013).…”
Section: Theoretical Backdrop Leadershipmentioning
confidence: 99%
“…Additionally, Sauer and Kohls (2011) propose that mindfulness may benefit leadership by contributing to improvements in information processing, interpersonal interactions, and decision making. Others have suggested that mindfulness contributes to emotional intelligence which, in turn, contributes to higher positive affect, lower negative affect, and greater life satisfaction (Schutte and Malouff, 2011;Smollan and Parry, 2011). Indeed, recent research shows that increasing mindfulness contributed to more job satisfaction and less stress as a result of increased ability to regulate one's emotions (Hülsheger et al, 2013).…”
Section: Theoretical Backdrop Leadershipmentioning
confidence: 99%
“…However, it is common to find that managers have the mistaken assumption that they can man-age and lead the organization and move employees regardless of their emotional aspects (Ashkanasy & Rush, 2004). Never the lees, employees are constantly perceiving how its managers express and manage their emotions if they respond appropriately to the emotions of their employees, managers are able to understand the emotions of their teams become a key issue for employees to share their emotions (Smollan & Parry, 2011). This situation is evident when the emotions of managers infect 2 employees producing the same emotions in them.…”
Section: Ei and Managementmentioning
confidence: 99%
“…8, No. 10;(Smollan, 2011. This acceptance particularly results with a very bright organizational change when the leader possesses appropriate communication and empathy skills (Cook, Macaulay, & Coldicott, 2004).…”
Section: The Significance Of Emotional and Spiritual Intelligencementioning
confidence: 99%